Government Policy in Providing Income Tax Facilities to Investment Companies Based on Government Regulation (PP) No. 62 Year 2008 - Puput Dini Lestari; Budiman Ginting; Mahmul Siregar (Institute Of computer Science (IOCS), 2022)
Investment facilities are provided taking into account the level of economic competitiveness and state financial conditions and must be promotive compared to facilities provided by other countries. Investment will only increase if a conducive and healthy investment climate is created and Indonesia's competitiveness is increased as an investment destination. For this reason, the government needs to issue an important policy for the country in facing the global financial crisis that is happening today in the form of providing tax incentives, especially income taxes for investment activities, where the policy is expected to strengthen Indonesia's position in facing the global financial crisis. The formulation of the problem in this thesis is a study of income tax based on Law no. 36 of 2008, policies on tax facilities in investment in order to encourage the creation of a conducive national business climate and can accelerate the increase in investment, as well as provisions for income tax facilities based on Government Regulation (PP) no. 62 of 2008 and the effect of government policies on income tax facilities on the Indonesian economy. The research method used is a normative legal research method. The normative legal research method is a research conducted by collecting data through library research. The written sources or materials used in the writing of this thesis are books, newspapers, and internet searches. Changes in income tax provisions in Law no. 36 of 2008 especially in terms of reducing the income tax rate on taxable income aimed at creating a competitive investment climate in Indonesia. Policy on tax facilities in investment to encourage the creation of a conducive investment climate to strengthen the competitiveness of the national economy. Provision of income tax facilities for investment as regulated in Government Regulation no. 62 of 2008 can stimulate investment that can encourage quality economic growth by absorbing a lot of workers.